Enriching Higher Education with Social Media: Development and Evaluation of a Social Media Toolkit - Yasemin Gülbahar (Athabasca University Press, 2017)
While ubiquitous in everyday use, in reality, social media usage within higher education teaching has expanded quite slowly. Analysis of social media usage of students and instructors for teaching, learning, and research purposes across four countries (Russia, Turkey, Germany, and Switzerland) showed that many higher education instructors actively use social media for private purposes. However, although they understand that their students also use it for learning purposes, and instructors sense the potential of social media in teaching, they mostly refrain from doing so due to various barriers. In response, an openly accessible trilingual Social Media Toolkit was developed which analyzes the teaching scenario with several questions, before suggesting, based on an algorithm, the best matching class of social media, complete with advice on how to use it for teaching purposes. This paper explains the rationale behind the toolkit, its development process, and examines instructors’ perceptions towards it.